2006
DOI: 10.1097/01.ccm.0000203103.11863.bc
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory care manpower issues

Abstract: This article provides a short history of the development of respiratory care and its historical relationship with critical care. We have, perhaps for the first time, provided a unified data set of key demographic information from the three professional bodies guiding the development of the respiratory therapy profession. This data set provides time-linked data on admissions and graduations from the CoARC, membership numbers for the AARC, and the numbers of active credentialed RCP from the NBRC. By two focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…The presence of a pharmacist in the ICU has been associated with reduced mortality, adverse events, infections, and drug charges (6165). The effect of changing the respiratory therapist:patient ratio has not been previously evaluated; expert opinion suggests that the optimal ratio of patients to respiratory care practitioners is between 9:1 and 11:1 (66). This may facilitate increased use of patient-oriented, respiratory care-driven protocols (6770).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a pharmacist in the ICU has been associated with reduced mortality, adverse events, infections, and drug charges (6165). The effect of changing the respiratory therapist:patient ratio has not been previously evaluated; expert opinion suggests that the optimal ratio of patients to respiratory care practitioners is between 9:1 and 11:1 (66). This may facilitate increased use of patient-oriented, respiratory care-driven protocols (6770).…”
Section: Discussionmentioning
confidence: 99%
“…A 2006 study, surveying RTs at 30 hospitals ranging in bed size from Ͻ 250 to Ͼ 500 beds, concluded that increased RT staffing would be necessary if ICUs continued to grow as projected. 27 A recommendation was made that one new RT be hired for every 11.3 beds added to an ICU, in order to maintain appropriate patient care. 27 Our study found that an improved RT staffing ratio of 1:10 (increased from 1:14) was associated with increased utilization of best-evidence practice in the care of mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the organizational model in the United Kingdom does not include respiratory therapists, thus organization and context must be considered when comparing nurse to patient ratios in other countries. 26 In the absence of respiratory therapists in the United Kingdom, it is essential that PICU nurses be used effectively and efficiently within the interprofessional team to manage the weaning process. Protocols assist bedside nurses in making decisions about the frequency and appropriateness of weaning and, in an adult ICU study, nurses found that protocols provided uniformity and safe guidance in weaning practice.…”
Section: Professional Responsible Senioritymentioning
confidence: 99%